ADVERSE DRUG REACTIONS REPORTING: KNOWLEDGE, ATTITUDE AND PRACTICE AMONG HEALTHCARE PROVIDERS AT A TERTIARY HOSPITAL IN NORTHERN REGION OF MALAYSIA - Roksanah Shaukat Ali; Wan Ismahanisa Ismail (Asian Journal of Medicine & Health Sciences, 2021)
Background: Adverse drug reaction (ADRs) underreporting is an excellent challenge to pharmacovigilance worldwide. Spontaneous and voluntary was the utilized system of ADRs reporting in Malaysia. Objective: This study aimed to identify the healthcare provider’s knowledge, attitude, practice, and factors associated with Malaysia’s ADR reporting system. Methods: A cross-sectional study was conducted using self-administered questionnaires among healthcare providers in Hospital Sultan Abdul Halim, Kedah. Descriptive statistics are utilized for selected variables. Results: A total of 332 study questionnaires were distributed, and 269 participants were duly filled, giving a response rate of 81.0%. There were 40.9% (n=110) pharmacists, 39.0% (n=105) doctors and 20.1% (n=54) nurses. Almost half of the participants knew how to define pharmacovigilance (n=137, 50.9%) and ADR (n=131, 48.7%). The majority of participants are aware of ADR reporting procedures (n=174, 64.7%) and ADR reporting center in Malaysia (n=207, 77.0%). Most of the participants agreed that reporting ADR is necessary (n=260, 96.6%), should be mandatory (n=252, 93.7%), and reporting ADR will increase patient safety (n=264, 98.1%). Among the participants who had reported an ADR, only 39.1% (n=45) reported all types of ADR. The most important factor that encouraged participants to report ADR was the seriousness of ADR (n=155, 57.6%). In contrast, a lack of knowledge on reporting ADR might discourage them from reporting ADRs (n=136, 50.6%). Conclusion: This study reveals that most participants have good knowledge, a positive attitude, and good practice towards ADR reporting in Malaysia. The continuous education and updates regarding ADRs, including the reporting procedures, were essential for improving ADR reporting and monitoring in enhancing medication safety.